Transaction Cost Analysis of Service Organization-Customer Exchange - Bowen, David E.; Jones, Gareth R. (Academy of Management Review, 1986)
Transaction cost analysis can explain the arrangements that emerge to govern and organize service organization-customer exchanges. A typology is offered in which differing governance mechanisms are matched to varying levels of transaction costs in service exchanges. The focus is on prescribing governance mechanisms that establish the most efficient boundary between the service organization and the customer, thereby improving service organization effectiveness.